Information asymmetry and insurance in Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2020)
In this study, we assess the relevance of decreasing information asymmetry on life and nonlife insurance consumption, by using data from 48 African countries during the period 2004-2014. Reduced information asymmetry is proxied by information sharing offices, namely: public credit registries and private credit bureaus. The empirical evidence is based on the Generalised Method of Moments. The findings show that information sharing offices increase insurance consumption with a comparatively higher magnitude in life insurance penetration, relative to non-life insurance penetration. Practical and theoretical implications are discussed.
Keywords: I30; G20; G22; O16; O55; 330; Insurance; Information Asymmetry